Principles of the Mechanism for Epimuscular Myofascial Loads Leading to Non-uniform Strain Distributions Along Muscle Fiber Direction: Finite Element Modeling - Pamuk, Uluç; Cankaya, Alican Onur; Yucesoy, Can A. (Frontiers in Physiology, 2020)
Sarcomere lengths and their changes are key determinants of muscle active force production. Recent studies indicate inhomogeneity of sarcomere lengths within the muscle. Studies utilizing magnetic resonance imaging (MRI) analyses for quantifying local muscle tissue strains and diffusion tensor imaging (DTI) analyses allowing for determination of their components along muscle fascicles show that those length changes can be non-uniform. Specifically, two questions arise regarding the muscle’s length change heterogeneities along the muscle fiber direction: (1) How can a passively lengthened muscle show shortened regions? (2) How can an isometric contracting muscle show lengthened parts? Using finite element modeling and studying principles of the mechanism of strain heterogeneity along the muscle fiber direction, the aim was to test the following hypothesis: epimuscular myofascial loads can lead locally to strains opposing those elsewhere within the muscle that are determined by the globally imposed conditions. The geometry of the model was defined by the contour of a longitudinal slice of the rat extensor digitorum longus (EDL) muscle belly. Three models were studied: (1) isolated muscle (muscle modeled fully isolated from its surroundings) and models aiming at representing the principles of a muscle in its in vivo context including (2) extramuscularly connected muscle (muscle’s connections to non-muscular structures are modeled exclusively) and (3) epimuscularly connected muscle (additionally muscle’s connections to neighboring muscle are modeled). Three cases were studied: passive isometric muscle with imposed relative position change (Case I), passive lengthened muscle (Case II), and active isometric muscle with imposed relative position change (Case III). The findings indicated non-uniform strains for all models except for zero strain in model (1) in Case I, but models (2) and (3) also showed strains opposing the imposed effect. Case I: model (3) showed shortened and lengthened sections (up to 35.3%), caused exclusively by imposed relative position change. Case II: models (2) and (3) showed shortened sections (up to 12.7 and 19.5%, respectively) in addition to lengthened sections. Case III: models (2) and (3) showed lengthened sections (up to 5 and 23.4%, respectively) in addition to shortened sections. These effects get more pronounced with stiffer epimuscular connections. Assessments of forces exerted on the muscle by the epimuscular connections showed that such strain heterogeneities are ascribed to epimuscular myofascial loads determined by muscle relative position changes.